INTERPRETATION AND VIEWS OF QURANIC COMMENTARIES ON THE PLANET BASED ON AL-KAWKAB AND AL-KAWAKIB TERMS - Wahid, Khairussaadah; Nawawi, Mohd Saiful Anwar Mohd; Man, Saadan (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
This paper examines the occurrence of the terms al-kawkab (plural, al-kawakib) in the Qur’an and investigates the views of classical and contemporary Quranic commentaries concerning the interpretation of the meanings of these terms. In general, the Qur’an uses al-kawkab as the singular term and al-kawakib as the plural term. The argument among Quranic commentaries concerning the interpretation of the meaning of al-kawkab (plural, al-kawakib) in the Quran revolve around whether it refers to either a planet or a star. Thus, this paper attempts to reconcile this contradiction in the meaning of al-kawkab (plural, al-kawakib) among Quranic commentaries by considering the Arabic lexical sources as well as the various Quranic allusions. The data collections involved library research based on the primary and secondary sources relating to the planets in the solar system. After examining the views on the Quranic commentaries, the authors conclude that the meaning of the term al-kawkab (plural, al-kawakib) in the Quran refers to a planet.